2009
DOI: 10.1007/s00239-009-9268-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Fit of Sequence Data to Phylogenetic Model: Gain of Power Using Marginal Tests

Abstract: field of phylogenetics rarely do this. Such analyses discard fundamental aspects of science as prescribed by Karl Popper. Indeed, not without cause, Popper (1978) once argued that evolutionary biology was unscientific as its hypotheses were untestable. Here we trace developments in assessing fit from Penny et al. (1982) to the present. We compare the general log-likelihood ratio (the G or G 2 statistic) statistic between the evolutionary tree model and the multinomial model with that of marginalized tests app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Additionally, some torsion procedures could represent cases of intermittent torsion, which is more likely to be treated on an outpatient basis. Small case series have reported that intermittent torsion represents 18–63% of all torsion[17, 18]. As no separate billing code for intermittent torsion exists, we could not confirm this hypothesis; however the lower proportion of subjects undergoing orchiectomy in the outpatient vs. inpatient setting suggests intermittent torsion could be a component influencing this pattern of care.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, some torsion procedures could represent cases of intermittent torsion, which is more likely to be treated on an outpatient basis. Small case series have reported that intermittent torsion represents 18–63% of all torsion[17, 18]. As no separate billing code for intermittent torsion exists, we could not confirm this hypothesis; however the lower proportion of subjects undergoing orchiectomy in the outpatient vs. inpatient setting suggests intermittent torsion could be a component influencing this pattern of care.…”
Section: Discussionmentioning
confidence: 89%
“…A consensus tree was obtained from BI trees for the 97-gene data set using the majrule command in Clann, version 3.0.0 (Creevey and McInerney 2005). Because standard Bayesian PP values can be very unreliable when an incorrect model is used, and nuclear mammalian genes show clear deviations in base composition and relative rates of substitution types from those of commonly employed models (Waddell et al 2009), we also implemented gene partitions and specified a model for each gene included in the Bayesian analyses of the 97-gene data set. Additionally, approximately unbiased (AU) tests (Shimodaira 2002) were conducted in Consel version 0.1 (Shimodaira and Hasegawa 2001) between the best ML tree and alternative topologies to evaluate whether their likelihoods were significantly different.…”
Section: Methodsmentioning
confidence: 99%
“…Marginal tests of base compositions between pairs of taxa (T avare 1986) have been found to be more powerful than the τ 2 goodness of fit test of the substitution models to phylogenetic data (W addell et al . 2009).…”
Section: Methodsmentioning
confidence: 99%